ERADICATION OF CRIMINAL ACT OF STEALING BY VIOLATING IN DELI TUA AREA - Marolop Marolop Marolop (jurnal.unprimdn.ac.id, 2018)
The objective of the study is to describe the efforts to eradicate violent theft by violence in the Delitua region. This research is used a juridical empirical research method that emphasizes the use of primary data from the results of interviews with the appropriate resource persons with the problem under study to obtain facts that occur in the field or research location. These data were analyzed using descriptive method by describing the symptoms in the community against a case under study. In this study, it is stated that there are some factors that cause theft by force; namely economic, environmental factors. education level, and Narcotics. Crime prevention policies issued are by following criminal law policies issued by Medan Police Resort Office that is Operation 810 (Shoot directly on the spot) and the efforts of The Delitua Police Sector to deal with violent crimes through preventive efforts; by gathering all security officers from companies and housing and providing counseling on how to protect the environment from strangers. The second preventive effort carried out is to improve the performance of the police, socialization and community approaches in order to create coordination and cooperation that synergizes in creating security.